A study of stress faced by parents of children with cerebral palsy - Leow, Stephenie Koon Miang. (2008)
This study aims to find out if differences exist between the levels and sources of stress, namely, parental distress (PD), parent-child dysfunctional interaction (P-CDI), and diffcult child (DC), between fathers and mothers of children with cerebral palsy in Singapore.